3PC-023 Gravimetric manufacturing of chemotherapy: optimising its place in production. (2nd March 2018) - Ryan, B; Gavin, P; Meegan, C
Abstract : Background: The MMUH employs a 'double check' system for chemotherapy manufacture. Using traditional volumetric manufacture the technician draws up the dose (check 1) and the pharmacist visually checks this (check 2). Gravimetric manufacture is a new technique using Computer Aided Technology for Oncology (CATO ® ), software integrated with electronic balances in the isolators. Technicians draw up the dose, completing check 1. Check 2 is electronically completed by CATO ® using drug density with pre- and post-manipulation weights of: syringe(s), infusion bag and vial(s). Purpose: To evaluate the time impact of gravimetric manufacture on different dosage forms and identify its optimal place within MMUH procedures and workflow. Material and methods: Design and pilot a data collection tool recording manufacture time from tray preparation, including sterilisation, gowning, production time, CATO data entry, * worksheet/label generation, * troubleshooting* and ending when the product exits the isolator. Exclusion: pharmacist time to check and generate worksheets/labels for volumetric manufacture. Measure volumetric and gravimetric manufacture time for bolus syringes, batch bolus syringes and infusion solutions. Compare results. Results: There was no statistical difference between volumetric and gravimetric compounding of one-step infusions (p=0.17) or batch of three syringes (p=0.1) (Table 1). Gravimetric bolus manufacture was slower for single syringes (p=0.0001) taking approximately twice as long and slower for batch of two syringes (p=0.001). Bolus gravimetric manufacture has ceased based on this data and the availability of a visual check at the final point of product release. Unmeasured benefits of reduced pharmacist interruptions and independent technician work make this method worthwhile. Conclusion: Gravimetric manufacture of one-step infusions is routinely employed, allowing greater flexibility of workflow for pharmacists and technicians. Gravimetric manufacture was substantially slower than volumetric manufacture for bolus syringes and is no longer in use. References and/or Acknowledgements: Patricia Ging No conflict of interest